1995
DOI: 10.1046/j.1469-0705.1995.05060391.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal pelvic kidney: a challenge in prenatal diagnosis?

Abstract: The objective of this study was to establish ultrasonographic guidelines for the prenatal diagnosis of fetal pelvic kidneys and assess the relationship to clinical outcome. The records of all ultrasonographic diagnoses of a fetal pelvic kidney between 1 January 1991 and 31 December 1993 were reviewed. After review of the sonographic evaluation, the prenatal records were obtained, to assess demographic data as well as the obstetric course and neonatal outcome. If a fetal pelvic kidney was suspected on prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…The prevalence of pelvic kidney is frequently quoted as 1 in 1,200 autopsies [9], although others postulate that this should be somewhat around 1 in 700 [10], as they are mostly asymptomatic. On the other hand the reported prevalence of fetal pelvic kidneys in previous series are 1 in 1,965 [11] and 1 in 1,112 fetuses [12]. We were not able to report the true incidence of renal agenesis and renal ectopia as well as the false negative rate of prenatal sonography in detecting these malformations, because routine sonographic examination of the urinary system in asymptomatic newborns is not part of our general health care system.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The prevalence of pelvic kidney is frequently quoted as 1 in 1,200 autopsies [9], although others postulate that this should be somewhat around 1 in 700 [10], as they are mostly asymptomatic. On the other hand the reported prevalence of fetal pelvic kidneys in previous series are 1 in 1,965 [11] and 1 in 1,112 fetuses [12]. We were not able to report the true incidence of renal agenesis and renal ectopia as well as the false negative rate of prenatal sonography in detecting these malformations, because routine sonographic examination of the urinary system in asymptomatic newborns is not part of our general health care system.…”
Section: Discussionmentioning
confidence: 56%
“…In their study, Hill et al classified pelvic kidneys according to their localization within the fetal pelvis either as ipsilateral or midline but did not describe the exact diagnostic criteria [11]. On the other hand, in reviewing their sonographic data, Meizner et al found that, in all cases with postnatally proven pelvic kidneys, these were located opposite the sacrum and below the aortic bifurcation [12]. Instead of using similar strict sonographic criteria, we have made the diagnosis of pelvic kidney if they were in close proximity to the fetal bladder ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral ectopia can be associated with imperforate anus and tracheoesophageal fistula (Cinman et al 2007). Prenatal diagnosis of pelvic kidney is available after 24 weeks of gestation (Meizner et al 1995). In men, associated genital abnormalities are seen in 10-20% of patients, including undescended testes, urethral duplication, and hypospadias (Kocak et al 2001).…”
Section: Signs Of Pelvic Kidneymentioning
confidence: 99%
“…Cross‐fused renal ectopia is an uncommon congenital anomaly, with an estimated prevalence of 1 per 1000 to 7500 autopsies 2 4 . Prior (postnatal) retrospective case studies suggest a male predominance (3:2) and a greater left‐to‐right crossover frequency 1 , 2 , 5 , 6 . This anomaly is theorized to result from abnormal development of the ureteric bud and metanephric blastema during the fourth to eighth weeks of gestation 2 , 6 .…”
mentioning
confidence: 99%
“…This anomaly is theorized to result from abnormal development of the ureteric bud and metanephric blastema during the fourth to eighth weeks of gestation 2 , 6 . Other theories regarding the etiology of cross‐fused renal ectopia include pressure from abnormally placed umbilical arteries, malrotation of the caudal end of the fetus, teratogenic factors, and genetic factors 5 , 6 …”
mentioning
confidence: 99%